Low‐Latitude Whistler‐Wave Spectra and Polarization From VEFI and CINDI Payloads on C/NOFS Satellite. Issue 1 (8th January 2020) - Jacobson, Abram R.; Holzworth, Robert H.; Pfaff, Robert; Heelis, Roderick
Abstract: The Communication/Navigation Outage Forecast System (C/NOFS) satellite's VEFI payload performed frequent recordings of the vector electric field in the band 0–16 kHz during the epoch 2008–2014. The Vector Electric Field Instrument (VEFI) was supported by ion‐composition data from the Coupled Ion Neutral Dynamics Investigation (CINDI) instrument. We focus here on statistics of these "burst‐mode" recordings, of which 6, 890 (mostly ~12‐s duration) records meet stringent quality‐control criteria, allowing inference of the wave vector k and its orientation relative to the Earth's magnetic field B 0 . The 6, 890 records occur between ±13° (geographic) latitude and between ~ 400‐ and 850‐km altitude, mostly in the topside ionosphere. The wave activity is dominated by terrestrial lightning. We analyze the whistler‐wave intensity and polarization for each pixel in the time‐frequency spectrogram for each record. We then gather weighted statistics on wave polarization, naturally weighted by wave intensity. In this manner we arrive at statistical results that represent the bulk of the energy flow due to whistler waves. Despite rather nonstationary statistics, we can reach three empirical results. We see no evidence of a low‐latitude suppression of whistler‐wave activity, in contrast to the predictions of models of transmission through a laminar ionosphere. The wave vector polar angle is always in the range 40° to 90° from parallel to B 0 . This indicates that the propagation at low latitudes is dominated by oblique, not ducted, whistlers. At the lowest magnetic latitudes, the wave vector polar angle with respect to B 0 becomes nearly 90°. Key Points: C/NOFS VEFI has recorded the vector electric field in the VLF range at altitudes 400–850 km and at low magnetic latitudes It is found that the whistler wave intensity does not drop off at the lowest magnetic latitudes, contrary to model expectations It is found that the bulk of the whistler energy flow is due to oblique propagation, not ducted propagation